Estimation of Soil Electrical Properties in a Multilayer Earth Model with Boundary Element Formulation. (8th August 2012) - Islam, T.; Chik, Z.; Mustafa, M. M.; Sanusi, H.
Abstract : This paper presents an efficient model for estimation of soil electric resistivity with depth and layer thickness in a multilayer earth structure. This model is the improvement of conventional two-layer earth model including Wenner resistivity formulations with boundary conditions. Two-layer soil model shows the limitations in specific soil characterizations of different layers with the interrelationships between soil apparent electrical resistivity ( ρ ) and several soil physical or chemical properties. In the multilayer soil model, the soil resistivity and electric potential at any points in multilayer anisotropic soil medium are expressed according to the variation of electric field intensity for geotechnical investigations. For most soils with varying layers, multilayer soil resistivity profile is therefore more suitable to get soil type, bulk density of compacted soil and to detect anomalous materials in soil. A boundary element formulation is implemented to show the multilayer soil model with boundary conditions in soil resistivity estimations. Numerical results of soil resistivity ratio and potential differences for different layers are presented to illustrate the application, accuracy, and efficiency of the proposed model. The nobility of the research is obtaining multilayer soil characterizations through soil electric properties in near surface soil profile.